Fatigue Behaviour of T Welded Joints Rehabilitated by Tungsten Inert Gas and Plasma Dressing - Ramalho, A. (2011)
This paper concerns a fatigue study on the effect of tungsten inert gas (TIG) and plasma dressing in non-load-carrying fillet welds of structural steel with medium strength. The fatigue tests were performed in three point bending at the main plate under constant amplitude loading, with a stress ratio of R = 0.05 and a frequency of 7 Hz. Fatigue results are presented in the form of nominal stress range versus fatigue life (S–N) curves obtained from the as welded joints and the TIG dressing joints at the welded toe. These results were compared with the ones obtained in repaired joints, where TIG and plasma dressing were applied at the welded toes, containing fatigue cracks with a depth of 3–5 mm in the main plate and through the plate thickness. A deficient repair was obtained by TIG dressing, caused by the excessive depth of the crack. A reasonable fatigue life benefits were obtained with plasma dressing. Good results were obtained with the TIG dressing technique for specimens with shallower initial defects (depth lesser than 2.5 mm). The fatigue life benefits were presented in terms of a gain parameter assessed using both experimental data and life predictions based on the fatigue crack propagation law.